Particularităţile declaraţiilor martorului anonim în procesul penal [Articol] - Caraman, Valeria (CEP USM, 2022)
This article addresses the issues relating to the use of anonymous witness statements. The general principles applicable to the anonymous witness set out by the ECtHR are analyzed. Moreover, there are highlighted certain sufficient justifying reasons for keeping the witness’sanonymity. Additionally, this article examines the ECtHR’s case law in relation to the terms „sole ordecisive evidence”, as well as the elements of counterbalancing factors.
Keywords: martor anonim